Break all the borders: separatism and the reshaping of the Middle East - Jüde, Johannes (International Affairs, 2019)

Contesting borders? The formation of Iraqi Kurdistan’s de facto state - Jüde, Johannes (International Affairs, 2017)
Created from Fastlane, Scopus look-up

Making or un-making states: when does war have formative effects? - Jüde, Johannes (European Journal of International Relations, 2022)
“War made the state, and the state made war” is Charles Tilly’s famous dictum that has become highly influential both in comparative macrosociology and in International Relations. An extensive literature suggests that this mechanism has played a pivotal role in European processes of state formation. However, its applicability to warfare in the Global South is controversial. While some argue that the relationship remains the same, others are skeptical of the effects of the bellicist mechanism. Against the background of the debate as to whether war makes or un-makes states in the Global South, this paper examines the conditions under which wars have formative effects and result in state-making. Revisiting the war-making/state-making paradigm, I argue that the mode of economic reproduction of “wielders of coercion” determines whether war has formative effects. Wielders of coercion, or more specifically, non-state armed movements may draw on (1) rents, (2) indirect extraction, or (3) direct extraction to sustain their economic base and organize coercion. However, they institutionalize and develop into a state-like organization only when they rely on direct extraction. To support these claims, I conduct a plausibility probe drawing on evidence from highly successful armed insurgencies: Eritrea’s EPLF, Somaliland’s SNM, and Namibia’s SWAPO. In sum, the bellicist relationship remains valid for the Global South, even if the conditions under which war makes states are rare. A more nuanced reading of the bellicist theory improves our understanding of the dynamics of state formation and decay in the post-colonial world.
CRIS-Team Scopus Importer:2021-11-05
Keywords: bellicist theory; conflict; Global South; insurgents; organization of coercion; State formation

The possibility of state formation and the limitations of liberal international state-building - Jüde, Johannes (Journal of International Relations and Development, 2020)
Today, pressing security problems result from fragile statehood, and thus state-building has become a core responsibility of the international community. Ideally, such an intervention provides a short-cut to consolidated statehood; however, de facto, it has often failed. Countless studies have analyzed mechanisms accounting for the success or failure of state-building, but no clear picture has yet emerged. Strikingly, the debate widely disregards the historical records of state formation, even though these interventions aim for similar results. Bringing a classical state formation perspective back in, this paper bridges the state-building/state formation divide in research and asks the question: how do successful processes of state formation develop and what do they tell us about state-building operations? I analyze two cases of successful endogenous state formation in a non-Western post-conflict context. Scholarly work explaining the development of statehood distinguishes two broad groups of arguments: bellicose and cooperative theories. I demonstrate that state formation in Eritrea resulted from imperatives of warfare, while the state in Somaliland is owed to an elite coalition. I argue that there is little scope to steer and advance such state formation trajectories by liberal interventionist state-building. The logic of these operations conflicts with the internal dynamics of the two pathways. However, less intrusive intervention might facilitate domestic coalitions.<br